Pengaruh Kualitas Produk dan Social Media Marketing Instagram terhadap Keputusan Pembelian Buket pada Barung Bouquet Kecamatan Tallunglipu Kabupaten Toraja Utara - Ira Utami Ramba’; Althon K. Pongtuluran; Chrismesi Pagiu (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The purpose of this study was to determine whether product quality and social media marketing instagram affect bouquet purchasing decisions at Barung Bouquet. The data collection procedures of this study are: Questionnaires and documentation. The data analysis technique is quantitative with multiple linear regression tests. The partial test results (T test) show that the variables of purchasing decisions and social media marketing instagram affect the decision to purchase a bouquet at Barung Bouquet. Meanwhile, the results of simultaneous testing (F test) show that the variables of product quality and social media marketing instagram affect the decision to purchase a bouquet at Barung Bouquet.